Physical properties of dihydric Alcohol-based deep eutectic solvent for integrated fuel oil desulfurization - Majid, M.F.B. (Elsevier Ltd, 2019)
A benign separation of sulfur-containing compounds (SCC) from fuel oil is crucial to produce ultra-low sulfur fuels for a cleaner environment. To achieve this, extractive desulfurization could be implemented with deep-eutectic solvent (DES) as extractor. 2 DES were synthesized from choline chloride and dihydric alcohols, which were 1, 2-ethanediol and 1, 4-butanediol. It was found that shorther alkyl chain DES has higher density and low viscosity compared to longer alkyl chain DES. Freezing point depression to form melt compound at room temperature was observed for both DES. In optimized conditions, ethanediol produce higher desulfurization efficiency (60.27), suggesting a new opportunity for DES to be used in alternative desulfurization technology. Â© 2019 Elsevier Ltd. All rights reserved.